Comparison of the effectiveness of low pressure pneumoperitoneum with profound muscle relaxation during laparoscopic donor nephrectomy to optimize the quality of recovery during the early post-operative phase: study protocol for a randomized controlled clinical trial - Özdemir-van Brunschot, Denise M. D. (Trials, 2015)
BACKGROUND: Since technique modifications of laparoscopic donor nephrectomy, e.g. retroperitoneoscopic donor nephrectomy or hand-assistance, have not shown significant benefit regarding safety or improvement of recovery, further research should focus on improving postoperative recovery. The use of low pressure pneumoperitoneum has shown to significantly reduce postoperative pain after laparoscopy. To facilitate the use of low pressure pneumoperitoneum, deep neuromuscular block will be used. METHODS/DESIGN: This trial is a phase IV, single center, double-blind, randomized controlled clinical trial in which 64 patients will be randomized to: low pressure pneumoperitoneum (6 mmHg) and deep neuromuscular block or normal pressure pneumoperitoneum (12 mmHg) and deep neuromuscular block. Deep neuromuscular block is defined as post tetanic count < 5. Primary outcome measurement will be Quality of Recovery-40 questionnaire (overall score) on day 1. DISCUSSION: This study is the first randomized study to assess the combination of low pressure pneumoperitoneum in combination with deep neuromuscular block from a patients’ perspective. The study findings may also be applicable for other laparoscopic procedures. TRIAL REGISTRATION: The trial was registered at trials.gov (NCT02146417) in July 2014.